A critical review on rice cultivation and mechanization level in Indian perspective - Guru, Prabhat K.; Sahu, Parmanand; Shukla, Prabhakar; Diwan, Pushpraj; Panwar, Ghanshyam; Tiwari, Priyanka; Nagori, Ankur; Carpenter, Gopal; Sanodiya, Rajeswar; Meena, Balveer Singh; Kumar, Manish; Rani, Anshika; et al. (Elsevier, 2025)
Present article explores the historical trend, current scenario, mechanization level and challenges for rice cultivation in India. Rice, a vital crop for sustenance and the economy, faces the challenge of meeting the needs of India's growing population and supporting small-scale farmers. The literature highlights the necessity of modernization in response to population growth, resource constraints, and the demand for increased agricultural productivity. It explores the adoption of modern mechanization techniques, particularly the growing use of tractors, in the context of India's predominantly small land holdings. The paper also made a critical discussion on three primary rice cultivation methods employed in Indian scenario and highlights an overview of the machinery used for various agricultural operations for rice cultivation. In addition, it assessed the pros and cons of mechanical rice transplanter and the emergence of direct seeding of rice as a cost-effective alternative. The research addresses the challenges and opportunities associated with mechanizing rice cultivation practices in India, emphasizing the critical role of weed, water, and nutrient management in realizing the full benefits of modernization.